Performance analytic model and method for CCF multi-channel mechanism - YAN Jun-rong; ZHANG Shun-yi; SUN Yan-fei; LI Jun (Tongxin xuebao)
According to the characteristics of common channel framework（CCF） multi-channel mechanism of 802.11s draft,a performance analytic model and method were proposed.Considering two states of assigning or no assigning common channel to transmit data existed in CCF,two performance analytic models based on common channel were proposed and throughput formulas were deduced,furthermore condition of state transition was presented.There were four parameters,such as data rate,payload,number of channels and number of stations,participating in the simulation of throughput.The simulation result shows that with increasing of data rate,increasing of number of stations and/or decreasing of payload,the number of channels needed decreases as state of assigning common channel transiting to state of no assigning common channel,and then the throughput of CCF reaches the maximum.